A Heterogeneous Hydrogen‐Evolution Catalyst Based on a Mesoporous Organosilica with a Diiron Catalytic Center Modelling [FeFe]‐Hydrogenase. Issue 21 (28th September 2018) - Himiyama, Tomoki; Waki, Minoru; Esquivel, Dolores; Onoda, Akira; Hayashi, Takashi; Van Der Voort, Pascal; Inagaki, Shinji
Abstract: A diiron [FeFe]‐hydrogenase model complex tethered with a maleimide group, FeFe1, was covalently grafted on the pore surface of a periodic mesoporous organosilica with thiol groups (SH‐PMO) to form an efficient heterogeneous hydrogen (H2 )‐evolution catalyst FeFe1 @PMO. The coordination structure of the FeFe1 complex and the ordered pore structure were almost completely preserved even after immobilization of FeFe1 on SH‐PMO. The FeFe1 @PMO promoted photocatalysis for H2 evolution in water containing a photosensitizer [Ru(bpy)3 ] 2+, with a turnover number (TON) of 310 over 120 min. The TON was greater than those of an analogous homogeneous FeFe1 catalyst (TON=180) and conventional diiron complexes immobilized on solid supports (TON=6–18). The increased TON for FeFe1 @PMO compared to the homogeneous FeFe1 was attributed to the improvement in the stability of the FeFe1 complex by immobilization on the pore surface of SH‐PMO. A [Ru(bpy)3 ] 2+ photosensitizer tethered with a maleimide (Ru1 ) was prepared and co‐immobilized on FeFe1 @PMO to form an all‐solid‐state photocatalyst FeFe1 ‐Ru1 @PMO. FeFe1 ‐Ru1 @PMO evolved H2 without the additional [Ru(bpy)3 ] 2+ photosensitizer, suggesting efficient photoinduced electron transfer from the immobilized Ru1 to the immobilized FeFe1 . Abstract : Holding tight : An [FeFe]‐hydrogenase model complex was covalently anchored to a periodic mesoporous organosilica. The resulting FeFe1 @PMO promoted photoinduced hydrogen evolution in water containing a photosensitizer [Ru(bpy)3 ] 2+, with a turnover number of 310 over 120 min. The TON was greater than those of an analogous homogeneous FeFe1 catalyst and conventional diiron complexes immobilized on solid supports.